The effectiveness of knowledge-sharing techniques and approaches in research funded by the National Institute for Health and Care Research (NIHR): a systematic review - Helen Baxter; Lindsay Bearne; Tracey Stone; Clare Thomas; Rachel Denholm; Sabi Redwood; Sarah Purdy; Alyson Louise Huntley (BMC, 2024)
Abstract Background The National Institute of Health and Care Research (NIHR), funds, enables and delivers world-leading health and social care research to improve people's health and wellbeing. To achieve this aim, effective knowledge sharing (two-way knowledge sharing between researchers and stakeholders to create new knowledge and enable change in policy and practice) is needed. To date, it is not known which knowledge sharing techniques and approaches are used or how effective these are in creating new knowledge that can lead to changes in policy and practice in NIHR funded studies. Methods In this restricted systematic review, electronic databases [MEDLINE, The Health Management Information Consortium (including the Department of Health's Library and Information Services and King's Fund Information and Library Services)] were searched for published NIHR funded studies that described knowledge sharing between researchers and other stakeholders. One researcher performed title and abstract, full paper screening and quality assessment (Critical Appraisal Skills Programme qualitative checklist) with a 20% sample independently screened by a second reviewer. A narrative synthesis was adopted. Results In total 9897 records were identified. After screening, 17 studies were included. Five explicit forms of knowledge sharing studies were identified: embedded models, knowledge brokering, stakeholder engagement and involvement of non-researchers in the research or service design process and organisational collaborative partnerships between universities and healthcare organisations. Collectively, the techniques and approaches included five types of stakeholders and worked with them at all stages of the research cycle, except the stage of formation of the research design and preparation of funding application. Seven studies (using four of the approaches) gave examples of new knowledge creation, but only one study (using an embedded model approach) gave an example of a resulting change in practice. The use of a theory, model or framework to explain the knowledge sharing process was identified in six studies. Conclusions Five knowledge sharing techniques and approaches were reported in the included NIHR funded studies, and seven studies identified the creation of new knowledge. However, there was little investigation of the effectiveness of these approaches in influencing change in practice or policy.